Ireland and America : Empire, Revolution, and Sovereignty - Cogliano, Francis D.; Griffin, Patrick, 1965- (Book collections on Project MUSE., 2021)
"Ireland and America: Empire, Revolution, and Sovereignty is a collection of essays examining the seventeenth and eighteenth centuries in the Atlantic, and the relationship between imperial reform and revolution through the prism of Ireland, America, and empire. By focusing on one in relation to the other as well as within an imperial whole, the volume uses a comparative angle to retell familiar stories and create new narratives of each place and of both places engaged over two centuries"--